Maternal attitudes and factors associated with the Human Papillomavirus (HPV) vaccination uptake among daughters - Graaff, Lounette (My University, 2020)
Introduction: The Human Papillomavirus(HPV) has been identified as the most prevalent causative agent of cervical cancer, especially among young, sexually active women. Regardless of the availability of the HPV vaccine, vaccine uptake among adolescents in South Africa and globally remain poor. Parental hesitancy has been cited as a major contributing factor towards the low vaccine uptake. Vaccine hesitancy among mothers of adolescent girls and policies to address this issue remains understudied in South Africa. Therefore, this study aimed to address a) the maternal socioeconomic and demographic factors; and b) maternal attitudes and beliefs that played a role in vaccine hesitancy among mothers of adolescent daughters (aged10–19).Methods: Data were gathered through an online survey. A link to the survey was posted on various social media platforms and advertised through the distribution of flyers in a suburb outside a big metropolitan area. The survey consisted of maternal socioeconomic-demographic questions; a general HPV knowledge scale; and the HPV Attitudes and Beliefs Scale (HABS). Data were analysed through descriptive statistics, Pearson’s chi-square, and Binary Logistic Regression. Results: Majority of mothers (n=198) were White, middle-aged, highly educated and came from high-middle income families. Vaccine uptake among girls was poor (32.2%). Daughters of mothers who were ever married were less likely to be vaccinated than those with mothers that were never married. Mothers from Catholic or Non-religious affiliations were more likely to vaccinate their daughters than Christian counterparts. Additionally, mothers who shared an income with their spouse were 76% less likely to have vaccinated their daughter. Overall level of knowledge of HPV among mothers was moderate to high. From the final regression, influence was the only predictor of vaccine uptake. Conclusion: Maternal age, race, and other socio-economic factors did not play a significant role in adolescent vaccine uptake. The strongest predictor for vaccine uptake in this study were influence among friends, family, and healthcare providers, as well as whether the mother perceived the vaccine to be easily accessible. Further recommendation was made to include a mixed method study, initiatives that target parental consent and communication, programs that include healthcare provider influence, the effect of paternal influence and male responsibility, and addressing the source and messaging of the vaccine to address parental hesitancy
A dissertation submitted to the Faculty of Humanities of the University of the Witwatersrand in partial fulfilment of the requirements for the Degree of Master of Arts in Social and Psychological Research, 2020